Influence of natural fiber rope wrapping techniques on the compressive response of recycled aggregate concrete circular columns - Krisada Chaiyasarn; Nakhorn Poovarodom; Ali Ejaz; A. W. M Ng; Qudeer Hussain; Panumas Saingam; Hisham Mohamad; Panuwat Joyklad (Results in Engineering, 2023)
The utilization of recycled waste in the production of new concrete raises significant concerns regarding the quality of the resulting concrete. One prominent drawback of recycled aggregate concrete (RAC) is its inferior mechanical properties compared to natural aggregate concrete. In this study, we examine the impact of hemp fiber rope (HFR) confinement on improving the compressive stress-strain behavior of RAC, specifically using recycled brick aggregates from fired-clay solid bricks (RAC-FCSB) as a partial substitute for natural coarse aggregates. Furthermore, we explore and compare the effectiveness of HFR confinement in the form of strips versus fully wrapped confinement. To conduct the experiments, a comprehensive framework was developed, involving a total of 32 cylindrical specimens. The parameters of interest included the configuration of HFR confinement (strips or full wrapping), the number of HFR layers, and the inherent strength of the concrete. The results indicate that HFR strips can significantly enhance the compressive stress-strain response. However, their performance falls short when compared to the fully wrapped HFR confinement. Nonetheless, HFR strips were able to enhance the peak compressive stress and strain of RAC-FCSB up to 204% and 190%, respectively. The second part of the study investigated the performance of existing models of HFR confinement in predicting the peak compressive stress and strain of RAC-FCSB. The deficiencies in existing models were highlighted, and new models based on non-linear regression analysis were proposed to accurately predict the peak compressive stress and strain of HFR-confined RAC-FCSB.
Keywords: Recycled Aggregate Concrete Performance; Structural Behavior of Reinforced Concrete; Innovations in Concrete and Construction Materials